Dimensions of the Subaxial Lateral Mass: A Systematic Review of Anatomic (Morphometric) Measurement Studies. Issue 6 (July 2019) - Schroeder, Gregory D.; Kepler, Christopher K.; McKenzie, James C.; Casper, David S.; Sutton, Ryan; Hecht, Andrew C.; O'Shaughnessy, Brian A.; Skelly, Andrea C.; Brodt, Erika D.; Vaccaro, Alexander R.
Abstract : Study Design: This was a systematic review. Objective: To review and synthesize information on subaxial lateral mass dimensions in order to determine the ideal starting point, trajectory, and size of a lateral mass screw. Summary of Background Data: The use of lateral mass instrumentation for posterior cervical decompression and fusion has become routine as these constructs have increased rigidity and fusion rates. Methods: A systematic search of Medline and EMBASE was conducted. Studies that provided subaxial cervical lateral mass measurements, distance to the facet, vertebral artery and neuroforamen and facet angle made either directly (eg, cadaver specimen) or from patient imaging were considered for inclusion. Pooled estimates of mean dimensions were reported with corresponding 95% confidence intervals. Stratified analysis based on level, sex, imaging plane, source (cadaver or imaging), and measurement method was done. Results: Of the 194 citations identified, 12 cadaver and 10 imaging studies were included. Pooled estimates for C3–C6 were generally consistent for lateral mass height (12.1 mm), width (12.0 mm), depth (10.8 mm), distance to the transverse foramen (11.8 mm), and distance to the nerve. C7 dimensions were most variable. Small sex-based differences in dimensions were noted for height (1.2 mm), width (1.3 mm), depth (0.43 mm), transverse foramen distance (0.9 mm), and nerve distance (0.3–0.8 mm). No firm conclusions regarding differences between measurements made on cadavers and those based on patient computed tomographic images are possible; findings were not consistent across dimensions. The overall strength of evidence is considered very low for all findings. Conclusions: Although estimates of height, width, and depth were generally consistent for C3–C6, C7 dimensions were variable. Small sex differences in dimensions may suggest that surgeons should use a slightly smaller screw in female patients. Firm conclusions regarding facet angulation, source of measurement, and method of measurement were not possible. Abstract : Supplemental Digital Content is available in the text.